2009
DOI: 10.1007/s11064-009-9956-1
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular Administration of Ouabain to Rats Changes the Expression of NMDA Receptor Subunits in Cerebral Cortex and Hippocampus

Abstract: Ouabain exerts neurotoxic action and activates the population of NMDA receptors. Herein the effect of ouabain on the expression of NMDA subunits was evaluated. Adult Wistar rats were administered intracerebroventricularly with 0.1, 10 and 100 nmol ouabain or saline solution (control). Two days later, membranes of cerebral cortex and hippocampus were isolated. Western blots with antibodies for the NMDA receptor subunits: NR1; NR2A; NR2B; NR2C and NR2D were carried out. In cerebral cortex, NR2D subunit increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
1
9
0
1
Order By: Relevance
“…Area-dependent effect had been observed after ouabain injection (1-100 nmol) on assaying the expression of NMDA subunits. Such treatment only produces in cerebral cortex some increase in the expression of NR1 subunit and NR2D subunit whereas in hippocampus it leads mainly to decreases in the expression of NR2A-NR2C NMDA subunits as well as to either increase or decrease of NR1 subunit according to the drug dose employed [20]. These results suggest that endobain E produced similar changes on the expression of NMDA receptor subunits and Na ?…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Area-dependent effect had been observed after ouabain injection (1-100 nmol) on assaying the expression of NMDA subunits. Such treatment only produces in cerebral cortex some increase in the expression of NR1 subunit and NR2D subunit whereas in hippocampus it leads mainly to decreases in the expression of NR2A-NR2C NMDA subunits as well as to either increase or decrease of NR1 subunit according to the drug dose employed [20]. These results suggest that endobain E produced similar changes on the expression of NMDA receptor subunits and Na ?…”
Section: Discussionmentioning
confidence: 77%
“…Taken jointly, findings indicated that ouabain and endogenous inhibitor endobain E differentially increased expression of NMDA receptor subunits [19,20] and that this effect was concomitant with changes in Na ? , K ?…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations